IN SILICO STUDY OF JATI (Tectona grandis) LEAF CONSTITUENTS AS TRADITIONAL WOUND CARE - Krisnamurti, Gabriella Chandrakirana; Sukmaningsih, Anak Agung Sagung Alit; Primiani, Cicilia Novi (SEAMEO BIOTROP, 2025)
HIGHLIGHTS- T. grandis leaf methanolic extract contains 82 compounds, with 17 being predominant.- Epigallocatechin 3-O cinnamate, epigallocatechin 3-O-p-coumarate, and tectograndinol predicted as the potential bioactive compounds in wound healing- Molecular docking suggests inhibitory activities against NF-κB, MMP-2, and MMP-9, and stimulatory activity against EGFR-1 that comparable to commercial drugs. ABSTRACTWound-healing process involves a physiological cascade to restore skin integrity, which includes inflammatory response, cell proliferation, and tissue reconstruction. Prolonged inflammation in wound-healing process may lead to a chronic wound stage. Proper wound care is needed to prevent wound-caused mortality. Several studies showed the potential of T. grandis leaf in wound-healing process. However, the bioactive compounds and the molecular mechanism of T. grandis leaf remains unknown. This study aimed to identify bioactive compounds and biological activity contained in T. grandis leaf extract as well as analyze its molecular mechanism in wound-healing process by conducting in silico study using NF-κB, MMP-2, MMP-9, and EGFR-1. Bioactive compounds of T. grandis leaf extract were identified with LC-MS. Three potential compounds, epigallocatechin 3-O cinnamate, epigallocatechin 3-O-p-coumarate, and tectograndinol, were selected based on the Pa score screening with the PASS prediction. Drug-likeness and pharmacokinetics properties of the selected compounds were virtually identified by SwissADME and Protox. The interactions of T. grandis bioactive compounds toward NF-κB, MMP-2, MMP-9, and EGFR-1 were compared to those of curcumin, phenytoin, and nitrofurazone as control. Molecular docking to identify the protein-ligand interaction was performed by Autodock Vina integrated in PyRx v.0.8. Among 82 bioactive compounds detected in the LC-MS analysis, epigallocatechin 3-O-cinnamate, epigallocatechin 3-O-p coumarate, and tectograndinol exhibited anti-inflammatory, antioxidant, free radical scavenger, and MMP-9 inhibitor activities. According to Lipinski’s rule of five, bioactive compounds are possible to be administered as medication. Molecular docking showed that bioactive compounds potentially bound to the active sites of NF-κB, MMP-2, and MMP-9, resulting in proteins inhibition. This study suggested that the wound-healing mechanism of T. grandis bioactive compounds were driven by EGFR-1 stimulation indicated by the ability of bioactive compounds to interact with EGFR-1 in similar manner to those of nitrofurazone. We concluded that bioactive compounds of T. grandis leaf extract has significant potential to be used as traditional wound treatment and therapy. These compounds demonstrated wound-healing activity in silico by interacting with the key molecular targets, including NF-κB, MMP-2, MMP-9, and EGFR-1.